Socialism. Report of a public discussion in the Queen's theatre, Christian street, Liverpool, May 5th, 6th, 7th, and 27th, 1840 . "on the five facts, and constitution and laws of human nature, as propounded by Robert Owen;" Mr. Bowes being at liberty to express his views of their inconsistency with Christianity. [...].; (Liverpool, 1840)
Pamphlet Volume.